Effect of the supplementation of conjugated linoleic acid (CLA) and the loss of weight in animals and human beigs - Gaze, Bárbara Soares (2012)
All over the world, the prevalence of people with overweight and obesity has increased in elapsing of the years. Its treatment and prevention are objective of study, therefore the obesity is already considered a problem of public health. Therefore, each more time, products that guarantee the loss of weight, appears. The conjugated linoleic acid seems to help to produce the effect of the loss of weight and maintenance of corporal weight e, for this reason, comes being object for many studies. Some differences in the results of the studies with animals and human beings occur, some adverse effect had been told. This revision presents an analysis of the most recent data of literature related to the conjugated linoleic acid,energy metabolism and loss of weight. The studies are still not conclusive, therefore different parameters are used with relation to the dose, isomer, duration of administration, methods for evaluation of the corporal composition, effectiveness and collateral effect, therefore, more studies are necessary to determine its security and effectiveness, so that if it can make the indication of the conjugated linoleic acid as a factor auxiliary in the treatment of the obesity.